Enrichment and Separation of Methane Gas by Vacuum Pressure Swing Adsorption - Tao Zhu; Ruonan Wang; Xing Zhang; Yiwei Han; Wenjing Bian; Yan Ma; Ming Xue (Adsorption Science & Technology)
In China, owing to the methane concentration being below 0.75%, the coal ventilation air methane (CVAM) is usually emitted directly into the atmosphere, rather than utilized, which not only causes huge waste of energy but also exerts potential hazards to the greenhouse effect. It is important and practicable to save costs of development and investment by simulating enrichment and separation of CVAM with an aim to improve the efficiency and recovery of adsorption separation. Above all, it will have important practical significance to the development of adsorption separation. In this paper, the experiment of the pressure swing adsorption process was carried out on double towers built by our laboratory, and the Aspen Adsorption was used to simulate the process. The effect of the operation parameters on the desorbed methane concentration was studied by altering the feed concentration, the adsorbed pressure, and adsorbed and desorbed time. The results of simulation and experiment are basically consistent. The ratio of methane was decreased following the increasing concentration of the feed. The optimum adsorption pressure and time were found to be 210 kPa and 120 s, respectively. The optimum desorption times of experiment and simulation were 150 s and 120 s, respectively. Because there was a man-made 30 s time lag between the experiment and simulation to protect the vacuum pump, the results show that the simulation and experiment were matched well. Therefore, we can make use of Aspen Adsorption to design separation and enrichment of CVAM, providing theoretical and practical guidance for the gas separation and saving resources and energy.